(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article discusses how using real videos for young learners in foreign language teaching is a highly effective way to engage students, improve their listening skills and teach them to use real-world languages, and how real videos can be used effectively.